An Efficient Micropropagation Protocol Of An Elite Clone Ec-353508 Of Artemisia Annua L., An Important Antimalarial Plant - GAURAV SHARMA; VINAY SHANKAR; VEENA AGRAWAL (International Journal of Pharma and Bio Sciences, 2011)
An efficient in vitro propagation system for an elite clone EC-353508 of Artemisia annua L., an important antimalarial drug plant has been developed. The best organogenic response, including adventitious multiple shoots and their elongation, was obtained when nodal explants were cultured on MS medium supplemented with 10µM 2-isopentenyl adenine (2iP). An average of 17.7±0.88 shoots with an average shoot length of 5.25±0.17 (cm) was differentiated per explant. Excised in vitro shoots organized roots in cent percent cultures when subcultured on half MS basal medium augmented with 5 µM α-naphthalene acetic acid (NAA). The plantlets were gradually hardened and transferred to sterile garden soil: soilrite (1:1) mixture for acclimatization. This is the first report of an efficient and cost effective protocol for direct shoot multiplication from nodal explants in an elite clone of Artemisia annua.